Empirical analysis of the constituent factors of internal marketing orientation at Spanish hotels - José Luis Ruizalba-Robledo; María Vallespín-Arán (Tourism & Management Studies)
This study, which draws upon specialized literature and empirical evidence, aims to characterize the underlying structure of the construct ‘Internal Marketing Orientation’ (IMO). As a consequence six underlying factors are identified: exchange of values, segmentation of the internal market, internal communication, management concern, implementation of management concern and training. It also evaluates the degree of Spanish hotels’ IMO, classifying them into three different groups according to their level of IMO. Findings indicate that a higher degree of IMO is found when the company belongs to a hotel chain, while no other variables such as hotel size or category have proven to be significant.